PENGENALAN PEMBUATAN PETA DAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI QUANTUM GEOGRAPHIC INFORMATION SYSTEM BAGI GURU GEOGRAFI SMA DI KOTA KENDARI PROVINSI SULAWESI TENGGARA - La Ode Hadini; Nurgiantoro Nurgiantoro; Amniar Ati (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The introduction of map making and at the same time as the development of learning media are the efforts to improve the performance of high school geography teachers in the learning process of geography. This activity aims to increase teacher knowledge in spatial data concepts and cartographic rules for learning geography. PKM activities are carried out in the form of training using lecture methods, demonstrations and online discussions. The methods is used in explaining the concepts of spatial data and cartographic rules in the form of understanding, subsystems, components, data, processes, analysis, and presentation. This training activity went well based on the achievement of the target of the training participants, the objectives of the training, and the target of the planned material, as well as the ability of the participants in mastering the material being trained. Supporters for the implementation of this PKM activity include the availability of experts in the field of Cartography and QGIS at the UHO Geography Department, the enthusiasm of the participants, and the available funds for the service team. The benefits that participants can get from PKM activities are applying QGIS in making maps and for developing geography learning media in high school education